Utility of Dexrazoxane for the Attenuation of Epirubicin-Induced Genetic Alterations in Mouse Germ Cells - Attia, Sabry M. (PLoS One, 2016)
Dexrazoxane has been approved to treat anthracycline-induced cardiomyopathy and extravasation. However, the effect of dexrazoxane on epirubicin-induced genetic alterations in germ cells has not yet been reported. Thus, the aim of this study was to determine whether dexrazoxane modulates epirubicin-induced genetic damage in the germ cells of male mice. Our results show that dexrazoxane was not genotoxic at the tested doses. Furthermore, it protected mouse germ cells against epirubicin-induced genetic alterations as detected by the reduction in disomic and diploid sperm, spermatogonial chromosomal aberrations, and abnormal sperm heads. The attenuating effect of dexrazoxane was greater at higher dose, indicating a dose-dependent effect. Moreover, sperm motility and count were ameliorated by dexrazoxane pretreatment. Epirubicin induced marked biochemical changes characteristic of oxidative DNA damage including elevated 8-hydroxy-2ʹ-deoxyguanosine levels and reduction in reduced glutathione. Pretreatment of mice with dexrazoxane before epirubicin challenge restored these altered endpoints. We conclude that dexrazoxane may efficiently mitigate the epirubicin insult in male germ cells, and prevent the enhanced risk of abnormal reproductive outcomes and associated health risks. Thus, pretreating patients with dexrazoxane prior to epirubicin may efficiently preserve not only sperm quality but also prevent the transmission of genetic damage to future generations.